2019
DOI: 10.1093/geront/gnz072
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Characteristics and Frailty: A Scoping Review

Abstract: Background and Objectives Frailty is highly prevalent in later life and associated with early mortality and adverse health outcomes. The neighborhood has been identified as an important contributor to individual health, and neighborhood characteristics may contribute to frailty development. A scoping review was conducted of the peer-reviewed literature to better understand how physical and social neighborhood characteristics contribute to frailty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…The World Health Organization (WHO) emphasized the role of the physical and social neighborhood environment for “healthy and active aging” in older adults in its guidelines of global age-friendly cities [ 7 , 8 ]. Many studies have previously reported that a poor neighborhood environment is associated with adverse health outcomes, including falls [ 9 ], disability [ 10 ], frailty [ 11 , 12 ], and mortality [ 13 ] all of which are known to be related to sarcopenia. Previous studies have reported that the neighborhood environment promotes healthy lifestyle habits, such as increased physical and social activity [ 13 , 14 , 15 ] and better dietary choices in older adults [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) emphasized the role of the physical and social neighborhood environment for “healthy and active aging” in older adults in its guidelines of global age-friendly cities [ 7 , 8 ]. Many studies have previously reported that a poor neighborhood environment is associated with adverse health outcomes, including falls [ 9 ], disability [ 10 ], frailty [ 11 , 12 ], and mortality [ 13 ] all of which are known to be related to sarcopenia. Previous studies have reported that the neighborhood environment promotes healthy lifestyle habits, such as increased physical and social activity [ 13 , 14 , 15 ] and better dietary choices in older adults [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…built environment, social cohesion, socioeconomic status, racial composition) in relation to frailty. 6 That review found a potential role of some social factors in residents' frailty. 6 Neighborhood-level deprivation was commonly used as a measure of social environments, and higher levels of deprivation were found to be associated with higher rates of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…2 Not everybody ages in the same way: age-related decline in physical and mental capacities and functional abilities are not homogenous. 3 Frailty is an age-related syndrome characterised as increased vulnerability, loss of resistance to stressors, and decreased reserves of capacity, which develops as a consequence of cumulative declines in several inter-related physiological systems. 4,5 Frailty among older people heightens the risk of falls, 6 morbidity 4 and mortality; 7 it is linked to increased healthand social-care costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence relied heavily on cross-sectional data and none of the identified investigations utilised repeated neighbourhood assessments through time. 3 Similarly, little is known about how neighbourhood-level factors are associated with frailty progression. 3,11 Places evolve All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation